Pruning methods on the yield performance and oenological potential of 'Nebbiolo' grapevine - Allebrandt, Ricardo; Marcon Filho, José Luiz; Würz, Douglas André; Pereira de Bem, Betina; Kretzschmar, Aike Anneliese; Rufato, Leo (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effect of different pruning methods on the yield performance and on the oenological potential of Vitis vinifera 'Nebbiolo', cultivated in high-altitude regions of Santa Catarina state, Brazil. The work was carried out in a commercial vineyard located in São Joaquim, SC, during the 2011/2012 and 2014/2015 crop seasons. The treatments consisted of four pruning systems: Guyot, Guyot Arch, and Cazenave (cane pruning systems), and cordon spur pruning. Production, vine balance, and grape composition were evaluated. In the cane pruning systems, a mean production of 2.0 kg per plant and Ravaz index below 2 were observed, with no change in the composition of the berries. In spur pruned vines, there was production only in 2015, with four bunches every ten plants. Yield and production of the 'Nebbiolo'grapes can be increased without losses of oenological potential, in the high-altitude regions of Santa Catarina state. The tested cane pruning methods are indicated for the growing of 'Nebbiolo' because all methods confer similar yield and vigor to this grapevine.
Keywords: Vitis vinifera; Guyot; Guyot Arch; Cazenave; Ravaz index; viticulture